2011
DOI: 10.1039/c0ce00716a
|View full text |Cite
|
Sign up to set email alerts
|

ZrTiO4 crystallisation in nanosized liquid–liquid phase-separation droplets in glass—a quantitative XANES study

Abstract: The crystallisation of the nucleation agent ZrTiO 4 in a low thermal-expansion lithium aluminosilicate glass-ceramics is monitored as a function of time by combining transmission electron microscopy with Ti-L 2,3 X-ray absorption near-edge structure spectroscopy. The formation of liquid-liquid phaseseparation droplets is shown to precede ZrTiO 4 crystallisation within the latter nanosized droplets. Quantitative data on crystalline fractions enable conclusions on the self-limited growth of ZrTiO 4 nanocrystals … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
62
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 62 publications
(68 citation statements)
references
References 26 publications
6
62
0
Order By: Relevance
“…The evolution of Ti 4 þ structural environment during nucleation has been also investigated by XAS at Ti K-edge [60,64] or L 2,3 -edges [64,65]. These studies have shown a coordination change from [5] Ti 4 þ to [6] Ti 4 þ due to the crystallization of ZrTiO 4 or aluminotitanate phases.…”
Section: Role Of Nucleating Agentsmentioning
confidence: 98%
“…The evolution of Ti 4 þ structural environment during nucleation has been also investigated by XAS at Ti K-edge [60,64] or L 2,3 -edges [64,65]. These studies have shown a coordination change from [5] Ti 4 þ to [6] Ti 4 þ due to the crystallization of ZrTiO 4 or aluminotitanate phases.…”
Section: Role Of Nucleating Agentsmentioning
confidence: 98%
“…In the case of glasses, the electronic microscopy is the method of choice for the observation of the initial nuclei. The smallest crystals observed by HRTEM have typically from 2 to 5 nm in diameter (Dargaud et al, 2010;Hoche et al, 2011;Stoch, 2008), without the possibility to assert whether they are critical germs because of the absence of in situ experiments allowing the observation of their appearance and disappearance. However, these sizes are in agreement with an estimation of the critical nuclei having several nanometers at high undercooling (Schmelzer et al, 2004).…”
Section: Direct Visualization Of Critical Nculeimentioning
confidence: 98%
“…Nucleation agents, either single or a combination of several, including TiO2, ZrO2, P2O5, and Ta2O5 have been used to produce a bulk nucleation owing to a liquid-liquid phase separation (Barbieri et al, 1997b;Guedes et al, 2001;Wurth et al, 2009;Ananthanarayanan et al, 2010;Li et al, 2010;Nemati et al, 2010;Höche et al, 2011;Höche et al, 2012;Montedo et al, 2012;Chavoutier et al, 2014;Kleebusch et al, 2016;Soares and Zanotto, 2016). Although minor in concentration, nucleation agents are critical to the final microstructure and properties of glass-ceramics.…”
Section: Discussionmentioning
confidence: 99%